Composing the Good Ship Hibernia and the hole in the bottom of the world - Roddy, Stephen (My University, 2017)
This paper explores topics in embodied cognition, soundscape composition and sonification. It explains the compositional decisions and technical considerations that went into the composition of the piece The Good Ship Hibernia, which is an example of embodied soundscape sonification. This explanation is undertaken within the context of an approach to both sonification design and music composition that accounts for and exploits the embodied aspects of meaning-making in auditory cognition as described in the embodied cognitive science literature.
PUBLISHED
Keywords: Data-driven; Music; Composition; Sonification; Financial Data